(untitled) (UNED Research Journal, 2022)
Introduction: Bioles are fermented liquid fertilizers. Objective: to evaluate the effect of a biol on soil characteristics and sprout production in pitahaya (Hylocereus sp.) cultivation. Methods: The evaluated treatments were Fertibiol 45L® and Control (distilled water), both applied to the soil. A physical, chemical and microbiological analysis of the soil was carried out before and towards the end of the trial. The production of new sprouts (vegetative and reproductive) was biweekly evaluated. Results: Compared to the Control, Fertibiol caused an increase in the content of P (+112%), S (+1200%) and Zn (+18%) in the soil, and a suppression of the fungi Penicillium sp. and Fusarium sp. Furthermore, it did not cause changes in the production of vegetative sprouts, but it did cause a decrease (-56%) in the production of reproductive sprouts of pitahaya. Conclusion: Fertibiol caused an improvement in the availability of P, S and Zn in the soil, and suppressed the fungi Penicillium sp. and Fusarium sp.; however, the production of reproductive sprouts was negatively affected in pitahaya cultivation, while the production of vegetative sprouts was not affected.